Curve Fitting of the Transport Behaviour of Epoxy Coated Fabrics through some selected Solvents - Francis N. Onuoha; Martin U. Obidiegwu; Genevive C. Onuegbu; Bibiana C. Aharanwa; Ezeamaku L. U (Journal of Fibers and Polymer Composites, 2026)
Modelling of the Transport Behaviour of selected solvents through Epoxy Coated Grey Fabrics had been carried out. The epoxy coated fabrics were formulated by coating the grey states of cotton (EC), nylon (EN), linen (EN), polyester (EP) with epoxy resin as published. 20ml of Hydrogen peroxide was mixed with colbalt and methyl ethyl ketone to form mixture 1, 20ml of borax was mixed with cobalt, and methyl ethyl ketone peroxide to form mixture 2. 40ml of epoxy was measured out in a beaker and poured into a basin and 20ml each of mixture 1 and 2 were injected gradually at different points in the basin. The grey fabrics were then dipped in each of mixtures to form epoxy coated grey fabric. The methyl ethyl ketone peroxide (MEKP) and cobalt were used as catalyst and accelerator respectively. The grey fabric were then dipped in the mixture of 1 and epoxy and 2 and epoxy to form epoxy coated grey fabrics and allowed to cool at room temperature. The epxy grey coated fabrics were totally immersed in water bath at temperatures of 18°C and 27°C at intervals of 300 seconds until equilibrium was reached. Sorption properties were calculated using the molar percentage uptake (qt) obtained from molar uptake at equilibrium (qe). The results obtained were validated using the least square technique with Matlab software. The epoxy grey coated fabrics were characterized using Scanning Electron Microscope (SEM) and Fourier Transport Infrared Spectroscopy (FTIR) to examine the internal structure, and functional groups. Results obtained indicated that the molar uptake of both composites followed the typical isotherm curves. The enthalpy of sorption obtained was positive and suggested Henrys type of sorption. The epoxy coated grey fabrics reached equilibrium at shortest time for the 18°C while 27°C took longer time. Elemental composition of the epoxy coated grey fabrics were obtained using the elemental dispersive X-Ray from SEM; they indicated presence of carbon, oxygen, sodium, potassium, silicon, calcium, aluminum, magnesium and iron.